BUSINESS INNOVATION AND CRITICAL SUCCESS FACTORS IN DIGITAL TRANSFORMATION AND CHALLENGING TIMES: AN ECONOMETRIC ANALYSIS OF STARTUP VIABILITY AND SUCCESS - Sikki, Nurhaeni; Aripin, Zaenal; Fitrianti, Nida Garnida (KRIEZ ACADEMY : Journal of development and community service, 2024)
This research reviews Business Innovation and Critical Success Factors in the context of the digital transformation period for startups. Through econometric analysis, this research explores the influence of business innovation factors, adaptation to technology, risk management, marketing strategy, and human resource management on startup survival and success. These factors are analyzed to understand the extent of their contribution in predicting startup performance in this challenging era. The research methodology involves collecting secondary data from a number of startups operating in various industrial sectors. Econometric analysis was carried out to measure the relationship between these factors and startup business performance. The research results highlight the importance of integrating business innovation, technology adaptation, careful risk management, responsive marketing strategies, and effective human resource management in increasing startup success amidst changes in the digital business paradigm.